2020
DOI: 10.1021/acsomega.9b03691
|View full text |Cite
|
Sign up to set email alerts
|

Copolymer of Pyrrole and 1,4-Butanediol Diglycidyl as an Efficient Additive Leveler for Through-Hole Copper Electroplating

Abstract: A copolymer comprising of pyrrole and 1,4-butanediol diglycidyl ether (PBDGE) was designed and synthesized as a leveler to improve the throwing power for printed circuit board (PCB) through-hole electroplating. The results of linear sweep voltammetry (LSV), galvanostatic measurements (GMs), and cyclic voltammetry (CV) reveal the strong coordination effect of PBDGE with other additives and confirm the advantageous performance of PBDGE to effectively assist the electroplating of through-hole. An increment of 35.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The energy gap (ΔE) should be calculated by ΔE = E LUMO − E HOMO . 40 It should be noted that the E HUMO values of ODA-ODPA and butadiene were close, implying that their HUMOs were prone to overlap, leading to a strong interaction. In comparison with butadiene, the smaller E LUMO and ΔE values of ODA-ODPA (−0.120 and 0121 eV) indicated that the ODA-ODPA oligomer had stronger interaction toward the copper surface and higher reactivity.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The energy gap (ΔE) should be calculated by ΔE = E LUMO − E HOMO . 40 It should be noted that the E HUMO values of ODA-ODPA and butadiene were close, implying that their HUMOs were prone to overlap, leading to a strong interaction. In comparison with butadiene, the smaller E LUMO and ΔE values of ODA-ODPA (−0.120 and 0121 eV) indicated that the ODA-ODPA oligomer had stronger interaction toward the copper surface and higher reactivity.…”
Section: Resultsmentioning
confidence: 96%
“…Generally, the electron transition was from the HOMO of the donor to the LUMO of the acceptor. The energy gap (Δ E ) should be calculated by Δ E = E LUMO – E HOMO . It should be noted that the E HUMO values of ODA-ODPA and butadiene were close, implying that their HUMOs were prone to overlap, leading to a strong interaction.…”
Section: Resultsmentioning
confidence: 99%
“…The throwing power ( TP ), a crucial indicator to characterize the thickness uniformity of the copper coating in the THs, was obtained according to the cross‐section images [46–48] . The throwing power ( TP ) value was calculated by the Equation (5).…”
Section: Methodsmentioning
confidence: 99%
“…The throwing power (TP), a crucial indicator to characterize the thickness uniformity of the copper coating in the THs, was obtained according to the cross-section images. [46][47][48] The throwing power (TP) value was calculated by the Equation ( 5). The H a , H b , H c , H d , H e and H f in the formula were the electroplated copper coating thickness presented in the Figure 8.…”
Section: Electroplating Experimentsmentioning
confidence: 99%
“…The surface evenness of the copper interconnects structure is important for achieving low transmission loss at high frequency. Now, copper electrodeposition technology of copper interconnected structure is based on the synergistic mechanism of organic additives to achieve the plating of interconnects structure in the acid copper electroplating system [3,4]. The organic additives can be mainly divided into three types, which are organic accelerators, inhibitors, and levelers [5,6].…”
Section: Introductionmentioning
confidence: 99%